Evaluation of the Relationship between Periodontal Indices and Blood Indices of Hematocrit and Hemoglobin in Patients Referring to the Cohort Center of Mashhad University of Medical Sciences - Naser Sargolzaie; Alireza Ghasemian; Ali Forouzanfar; Maryam sadat Daneshmand; Abdollah Javan (Mashhad University of Medical Sciences, 2022)
Introduction: Periodontal inflammation, which is one of the most common infectious diseases, can be caused by poor oral hygiene and microbial plaque, and the resulting inflammatory products can also lead to systemic effects on the peripheral blood system. The present study aimed to investigate the relationship of periodontal indices with hematocrit and hemoglobin in patientsMaterials & Methods: This cross-sectional observational study was performed on those referring to Mashhad University of Medical Sciences Cohort Center with a complete file. Firstly, patients' periodontal indices, including the Community Periodontal Index of Treatment Needs (CPITN) and Löe-Silness gingival index (GI), were extracted from the existing record files. These individuals were assigned to three groups according to the CPITN variable. Individuals with CPITN zero were considered a healthy group, individuals with CPITN 1 and 2 as a gingivitis group, and individuals with a CPITN of 3 or 4 as a periodontitis group. Blood indices (hemoglobin, hematocrit) were also extracted from patients' records. Thereafter, the relationship of hematocrit and hemoglobin with their periodontal indices was investigated using statistical tests.Results: In this study, the records of 242 participants, including 158 females and 84 males, were examined, out of whom 87 cases were healthy, 89 had gingivitis, and 68 had periodontits. In males and females, there were no significant differences between mean hemoglobin; however, the mean hematocrit of men in the healthy group was significantly higher than that in the gingivitis group. The mean of hematocrit were 2.4± 45.7 and 2.7±43.3 in the healthy and gingivitis groups, respectively. Nonetheless, in females, GI displayed no association with hematocrit or hemoglobin in either group.Conclusion: There was no significant difference between blood indices and periodontal disease in this study. In men, there was no significant difference in mean hemoglobin; nonetheless, the mean hematocrit was significantly higher in the healthy group than that in the gingivitis group. However, in females, there was no significant difference between mean hematocrit and hemoglobin. No correlation was detected between GI and hematocrit or hemoglobin in either group. Predictive regression analysis illustrated that for each unit increase in GI, the average hematocrit would be 0.37 units lower; however, no significant relationship was found between GI and hemoglobin.